(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the article is to select the most beneficial mortgage offer among bank offers in Koszalin as well as to select credit parameters favoring the choice of suitable mortgage offer. To achieve the goal, a research problem has been defined in the form of a scientific question: Do the basic parameters of mortgage translate into the selection of the most beneficial mortgage offer from the point of view of the total cost of credit?